Acceptance and Commitment Therapy for Trichotillomania: A Randomized Controlled Trial of Adults and Adolescents. Issue 1 (January 2020) - Lee, Eric B.; Homan, Kendra J.; Morrison, Kate L.; Ong, Clarissa W.; Levin, Michael E.; Twohig, Michael P.
The purpose of this study was to examine acceptance and commitment therapy (ACT) as a standalone treatment for trichotillomania in a randomized controlled trial of adults and adolescents. Participants consisted of a community sample of treatment seeking adults and adolescents with trichotillomania. Of the eligible 39 participants randomized into treatment and waitlist groups, 25 completed treatment and were included in the final analysis. Treatment consisted of a 10-session ACT protocol. Multiple mixed models repeated measures analyses were utilized to evaluate changes in trichotillomania symptom severity, daily number of hairs pulled and urges experienced, and experiential avoidance from pretreatment to posttreatment. Findings indicated significant changes in symptom severity and daily hairs pulled, but not daily urges experienced or psychological flexibility. However, psychological flexibility saw a 24.5% decrease in the treatment group and reduced from clinical to subclinical levels on average. This study suggests that ACT alone is an effective treatment for adults and adolescents with trichotillomania. Outcomes appear to be similar to trials that combined ACT and habit reversal training (HRT).